Single-Particle Dynamics at the Intrinsic Surface of Aqueous Alkali Halide Solutions - Hantal, György; Kolafa, Jiří; Sega, Marcello; Jedlovszky, Pál (The journal of physical chemistry. B, 2021)
The distribution of ions in the proximity of the liquid–vapor interface of their aqueous solution has been the subject of an intense debate during the last decade. The effects of ionic polarizability have been one of its salient aspects. Much less has been said about the corresponding dynamical properties, which are substantially unexplored. Here, we investigate the single-particle dynamics at the liquid–vapor interface of several alkali halide solutions, using molecular dynamics simulations with polarizable and nonpolarizable force fields and intrinsic surface analysis. We analyze the diffusion coefficient, residence time, and velocity autocorrelation function of water and ions and investigate how these properties depend on the molecular layer where they reside. While anions are found in the first molecular layer for relatively long times, cations are only making quick excursions into it, thanks to thermal fluctuations. The in-layer residence time of ions and their molar fraction in the layer turned out to be linearly dependent on each other. We interpret this unexpected result using a simple two-state model. In addition, we found that, unlike water and other neat molecular liquids that show a different diffusion mechanism at the surface than in the bulk of their liquid phase, ions do not enjoy enhanced mobility in the surface layer of their aqueous solution. This result indicates that ions in the surface layer are shielded by their nearest water neighbors from being exposed to the vapor phase as much as possible. Such positions are available for the ions at the negatively curved troughs of the molecularly rugged liquid surface.